Accounting ethics education : teaching virtues and values - Pinheiro, Margarida M., 1961-; Costa, Alberto J. (New York : Routledge, 2021)
Accounting Ethics Education: Teaching Virtues and Values gathers a diversity of contributions from invited, well-known experts. It promotes a comprehensive reflection around how ethics can and should be taught to accounting students, discussing and highlighting the most updated research on accounting ethics education, and it is an essential reference in the field. The subject of accounting ethics education is critical to foster ethical awareness that may prevent the way in which one acts or behaves, especially towards others. The point is that accounting education cannot exist without ethical education and accountants must be technically proficient and ethically sensible since ethical behavior is vital to the status and credibility of the accountancy profession. And this sensibility must be developed while the future professional is still cultivating his or her moral and intellectual structure within the school learning environment: character and practical reasoning are crucial because they include not only knowledge of rules and principles, and their correct application but also values and virtues. Examining multiple perspectives, Accounting Ethics Education: Teaching Virtues and Values advances the scholarly debate by providing cuttingedge and insightful research vital for all those interested and immersed in these matters. It begins with a historical perspective of accounting ethics education and continues by exploring challenges, opportunities and developments in the area. It will be of great value to academics, students, researchers and professionals in the fields of accounting, accounting education and ethics.
OCLC-licensed vendor bibliographic record.
Keywords: Accounting -- Study and teaching; Accounting -- Moral and ethical aspects; Accountants -- Professional ethics; BUSINESS & ECONOMICS / Accounting / General; BUSINESS & ECONOMICS / Accounting / Managerial; BUSINESS & ECONOMICS / Business Ethics